Business cycle synchronization in the EMU: Core vs. periphery - Ansgar Belke; Clemens Domnick; Daniel Gros (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
This paper examines business cycle synchronization in the European Monetary Union with a special focus on the core-periphery pattern in the aftermath of the crisis. Using a quarterly index for business cycle synchronization by Cerqueira (2013), our panel data estimates suggest that it is countries belonging to the core that are faced with increased synchronization among themselves after 2007Q4, whereas peripheral countries decreased synchronization with regards to the core, non-EMU countries and among themselves. Correlation coefficients and nonparametric local polynomial regressions corroborate these findings. The usual focus on co-movements and correlations might be misleading, however, since we also find large differences in the amplitude of national cycles. A strong common cycle can thus lead to large differences in cyclical positions even if national cycles are strongly correlated. – – Dieser Beitrag analysiert die Synchronisierung der Konjunkturzyklen in der Europäischen Währungsunion (EWU) mit Fokus auf das Kern-Peripherie Paradigma seit Ausbruch der globalen Finanzkrise. Eine hohe Korrelation der Konjunkturzyklen innerhalb einer Währungsunion ist wünschenswert, unter anderem um die Stabilisierungsfunktion der Geldpolitik zu erleichtern. Auf Basis eines vierteljährlichen Korrelationsindex von Cerqueira (2013) zeigen unsere Panelschätzungen, dass sich die Korrelation der Konjunkturzyklen innerhalb der Kernländer seit 2007Q4 erhöht hat. Im selben Beobachtungszeitraum hat die Synchronisierung der Konjunkturzyklen der Peripherieländer sowohl untereinander als auch im Vergleich zu anderen Referenzgruppen (Kern-, EWU- als auch nicht-EWU-Länder) jedoch abgenommen. Korrelationskoeffizienten sowie nichtparametrische Schätzungen bestätigen diese Ergebnisse. Neben der abnehmenden Synchronisierung finden wir große Unterschiede in den Amplituden der nationalen Konjunkturzyklen, welche die Durchführung der gemeinsamen Geldpolitik erschweren.
Keywords: E32; F15; R23; 330; business cycles; core-periphery; EMU; local polynomial regressions; synchronicity; common monetary policy